Painong San, a Traditional Chinese Compound Herbal Medicine, Restores Colon Barrier Function on DSS-Induced Colitis in Mice. (20th December 2021) - Rui, Xuelin; Li, Jiacheng; Yang, Ye; Xu, Li; Liu, Yang; Zhang, Mengmeng; Yin, Dengke
Abstract : Objective . The intestinal barrier decreases in colitis and restores the integrity of the mucosal barriers that could be used for the treatment of colitis. Painong San (PNS), a traditional Chinese compound herbal medicine originally recorded in "Jingui Yaolve" by Zhongjing Zhang in the Later Han Dynasty, is often used in China and Japan to treat various purulent diseases including intestinal carbuncle. This study was to investigate the effect of PNS on mucosal barrier function in mice with DSS-induced colitis and its related mechanisms. Methods . BALB/C mice were given 3% DSS to induce colitis. The body weight and stool status of the mice were recorded daily, and the histopathological changes of the colon were observed after execution. The permeability of the intestinal mucosa was measured by fluorescein isothiocyanate-dextran 4000, the change of intestinal microbiota was measured by 16S rDNA, and the tight junction-related proteins and Muc-2 were investigated by immunohistochemical or immunofluorescence. The possible signaling pathways were detected by western blot. Results . Compared with the control group, the composition of the microbiota in the PNS group was close to that of the normal group, the number of goblet cells was improved, and the mucosal permeability was significantly reduced. PNS could upregulate the expression of tight junction-related proteins (ZO-1, claudin-1, and occludin) and Muc-2, and at the same time, regulate the Notch pathway. Conclusion . PNS could effectively improve the mucosal barrier function through multiple ways, including restoring the balance of intestine flora, enhancement of the mucous layer barrier, and mechanical barrier function. These protective effects may relate to inhibiting the Notch signaling pathway activated by DSS.